Day-care centres for older migrants: spaces to translate practices in the care landscape. (12th February 2022) - Carlsson, Hanna; Pijpers, Roos; Van Melik, Rianne
ABSTRACT: Aging populations in Western Europe are increasingly culturally diverse, which raises the question how current care landscapes can meet differentiated care needs. Our study focuses on one possible response: culturally-specific day-care centres for older migrants. By drawing upon practice theory, the paper explores the potential of such centres to shape and be shaped by practices in the wider care landscape. Extensive participant observation and interviews with older clients, managers and professionals, allowed us to zoom in on the 'doing of care' in culturally-specific day-care centres in Nijmegen, the Netherlands. To zoom out on the wider care landscape, we conducted interviews with municipal policy advisors and a day-care coordinator, and engaged in further participant organisation in city-wide events on older migrants and cultural diversity. We find that culturally-specific day-care centres offer staff the opportunity to transform the practice of care. The day-care centres become spaces of interpretation and translation, through which staff connects their clients to other actors in the landscape, such as the municipality and other care providers. Although interpretations and negotiations within culturally-specific care spaces create some creative tension, these spaces potentially increase the responsiveness to cultural diversity of care practices in the care landscape of Nijmegen.